Kompatibilitas Penambahan Wet Scrubber Untuk Pengurangan Kandungan Tar Pada Downdraft Gasifier - Achmad Aziizudin (Institut Teknologi Adhi Tama Surabaya, 2022)
The amount of energy needed for daily needs causes fossil energy sources to decrease, so that efforts to develop other energy sources continue to be carried out. Biomass that has undergone further processing can be a renewable energy source. Gasification is one of the processes of processing biomass into a source of energy in the form of gas, but during this process there will be a lot of tar content produced. The amount of tar content needs to be adjusted to the standard tar content in the produced gas. The purpose of this study was to determine, analyze, and understand the effect of adding a wet scrubber to the tar content produced with rice husks as biomass. The provision of water discharge variations of 1.5 lpm, 2 lpm, and 2.5 lpm, as well as the position of the nozzle which is varied in its placement into horizontal, vertical, and collaboration, aims to determine the discharge and compatible nozzle position on the gasifier, which is seen from the tar content. contained in producer gas. The results of this gasification research will be compared with the gasifier without the addition of a wet scrubber.